Mycorrhizal fungi of endangered orchid species in Kolli, a part of Eastern Ghat’s, South India - Senthilkumar, S. (Universidad de Costa Rica, 2016)
The fascinating orchid flowers exhibit diversity in shape, structure, size, colour and fragrance which also account for multimillion dollar floriculture trade worldwide. The importance of mycorrhizal infection for the germination of orchid seeds and for successful development is well established.